Morphosyntactic Analysis of Political News on Online Tempo - Nurdiani, Pertiwi Rini; Fauzan, Umar (Yayasan Visi Intan Permata, 2020)
Morphology and Syntax are very important studies in learning English. Morphology learns about how the words are structured and how they are put together from smaller part. It can be considered as the grammar of words. Meanwhile, Syntax discusses how the sentence is structured. The objectives of the research are to find out inflectional morphemes, derivational morphemes, and the patterns of clause structure which are found in political news on online Tempo in January 2019. This research used qualitative design and content analysis design where the source of data was article political news on Online Tempo in January, 2019. The major instrument of this research is the researchers themselves because they actively obtained and clustered the data and the secondary data was data sheet. The findings revealed three types of morphosyntactic, firstly, the researchers found 5 patterns of inflectional morpheme with 26 words. The most dominant pattern of inflectional morpheme was singular changing to the plural. Secondly, for derivational morpheme, it identified two typesÂ of classes including class-changing and class-mantaining. There were 3 patterns with 10 words in class-changing and 1 pattern with 1 word in class-mantaining. The study also showed that the common pattern of derivational morpheme was class-changing pattern (verb to noun). Thirdly, there were 7 patterns with 15 clauses that were used in political news. The result of this study proved that the dominant pattern of clause structure was S-V- to Infinitive pattern with 4 clauses.